Kajian Perkembangan Islam di Negeri Melaka Melalui Pemetaan Masjid Warisan Menggunakan Kaedah GIS - Noor Faizah Binti Zohardin; Ahmad Yusof Bin Sahdan; Jusmine Hanis Binti Abdullah (LPPM Politeknik Jambi, 2023)
Malacca is renowned as a center for the rapid development and spread of Islam around the 15th century. The construction of mosques during that period served as places for the unity of Muslims and centers for the dissemination of knowledge. Mapping the location of these heritage mosques is important in identifying the early locations of Islam's spread in Malacca. Approximately 57 mosques have been designated as heritage mosques in Malacca by the Melaka Museum Corporation (PERZIM). Heritage mosques are those that are over 50 years old and still maintain their original characteristics. This study was conducted to map the locations of these heritage mosques using the Geographic Information System (GIS) method. All spatial location information and mosque database attributes will be organized to facilitate various analyses from the data. The data on mosques arranged using GIS methods can be analyzed more comprehensively, especially regarding the development of Islam in Malacca. The trajectory of Islam's development in Malacca can be clearly seen through the mapping of identified heritage mosques. Findings from the study indicate that Islam originated and focused on the coastal areas of Malacca before 1900 and began to spread throughout the state of Malacca after 1900.